2010
DOI: 10.1073/pnas.0912664107
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin suppresses microscopic hopping of T7 DNA polymerase on duplex DNA

Abstract: The DNA polymerases involved in DNA replication achieve high processivity of nucleotide incorporation by forming a complex with processivity factors. A model system for replicative DNA polymerases, the bacteriophage T7 DNA polymerase (gp5), encoded by gene 5, forms a tight, 1∶1 complex with Escherichia coli thioredoxin. By a mechanism that is not fully understood, thioredoxin acts as a processivity factor and converts gp5 from a distributive polymerase into a highly processive one. We use a single-molecule ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 31 publications
(34 reference statements)
5
41
2
Order By: Relevance
“…Polymerase labeling reactions were performed according to the procedure described by Etson et al (39) with an excess of either Alexa Fluor 488 carboxylic acid succinimidyl ester (Invitrogen) or Cy5 NHS ester (Lumiprobe) for an hour at room temperature. The conjugation reactions were biased to the N-terminal groups by adjusting the pH to 7.6.…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase labeling reactions were performed according to the procedure described by Etson et al (39) with an excess of either Alexa Fluor 488 carboxylic acid succinimidyl ester (Invitrogen) or Cy5 NHS ester (Lumiprobe) for an hour at room temperature. The conjugation reactions were biased to the N-terminal groups by adjusting the pH to 7.6.…”
Section: Methodsmentioning
confidence: 99%
“…These studies and the proper credits are well recorded in not-too-distant reviews (148)(149)(150)(151). The outstanding individuals who participated in these studies and are mentioned only briefly elsewhere include Barak Akabayov (143,(152)(153)(154)(155)(156)(157)(158), Nathalie Andraos (159) (149,180,181,(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197), Zhengguo He (198,199), Alfredo Hernandez (200), Anna Hine (201,202), Edel Hyland (203), Don Johnson (157,168,187,190,204,205), Young-Tae Kim (206)(207)(208)(209), Robin Kremsdorf (210), Arek Kulczyk (143,153,155,183,…”
Section: The T7 Replisomementioning
confidence: 98%
“…J.B. Lee determined the rate of movement of the polymerase and helicase and showed that primer synthesis temporarily halts leading-strand synthesis (191). C. Etson used these techniques to show that thioredoxin, the processivity factor, suppresses microscopic hopping by the polymerase (186). Sam Hamdan, a research fellow in my lab, joined Antoine's group and showed that leading-and lagging-strand synthesis was coordinated with the formation and resolution of replication loops (188).…”
Section: Movement Of the Replisome: Real-time Single-molecule Techniquesmentioning
confidence: 99%
“…The T7 system is even simpler, comprising only a polymerase (gp5), a combined helicase-primase (gp4) and an SSB (gp2.5) 30 . The Escherichia coli host protein thioredoxin is bound by the T7 polymerase and used as a processivity factor 78 . Single-molecule experiments have revealed key aspects of the T4 and T7 replication mechanisms that are likely to be conserved in bacteria.…”
Section: Box 1 | Single-molecule Studies Of Bacteriophage Replisomesmentioning
confidence: 99%